Responsiveness to oral prednisolone in severe asthma is related to the degree of eosinophilic airway inflammation. Issue 7 (16th June 2017) - Sousa, A. R.; Marshall, R. P.; Warnock, L. C.; Bolton, S.; Hastie, A.; Symon, F.; Hargadon, B.; Marshall, H.; Richardson, M.; Brightling, C. E.; Haldar, P.; Milone, R.; et al.
Summary: Background: Patients with severe asthma appear relatively corticosteroid resistant. Corticosteroid responsiveness is closely related to the degree of eosinophilic airway inflammation. The extent to which eosinophilic airway inflammation in severe asthma responds to treatment with systemic corticosteroids is not clear. Objective: To relate the physiological and inflammatory response to systemic corticosteroids in asthma to disease severity and the baseline extent of eosinophilic inflammation. Methods: Patients with mild/moderate and severe asthma were investigated before and after 2 weeks of oral prednisolone (Clintrials.gov NCT00331058 and NCT00327197). We pooled the results from two studies with common protocols. The US study contained two independent centres and the UK one independent centre. The effect of oral corticosteroids on FEV1, Pc20, airway inflammation and serum cytokines was investigated. Baseline measurements were compared with healthy subjects. Results: Thirty‐two mild/moderate asthmatics, 50 severe asthmatics and 35 healthy subjects took part. At baseline, both groups of asthmatics had a lower FEV1 and Pc20 and increased eosinophilic inflammation compared to healthy subjects. The severe group had a lower FEV1 and more eosinophilic inflammation compared to mild/moderate asthmatics. Oral prednisolone caused a similar degree of suppression of eosinophilic inflammation in all compartments in both groups of asthmatics. There were small improvements in FEV1 and Pc20 for both mild/ moderate and severe asthmatics with a correlation between the baseline eosinophilic inflammation and the change in FEV1 . There was a 50% reduction in the serum concentration of CXCL10 (IP‐10), CCL22 (MDC), CCL17 (TARC), CCL‐2 (MCP‐1) and CCL‐13 (MCP‐4) in both asthma groups after oral corticosteroids. Conclusions and Clinical Relevance: Disease severity does not influence the response to systemic corticosteroids. The study does not therefore support the concept that severe asthma is associated with corticosteroid resistance. Only baseline eosinophilic inflammation was associated with the physiological response to corticosteroids, confirming the importance of measuring eosinophilic inflammation to guide corticosteroid use.